1992
DOI: 10.1159/000457481
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Excretion of Drugs in Children: Theoretical and Practical Issues in Therapeutic Drug Monitoring

Abstract: Studies suggest that saliva could be used instead of blood in the therapeutic monitoring of many drugs. This has distinct advantages in pediatrics and neonatology as saliva sampling is painless and spares blood. Stimulation of saliva secretion with a chemical stimulus (i.e. citric acid applied over the tongue) facilitates the study of younger patients. Secretory and reabsorptive processes which take place in the ductal system of the salivary glands, and the rate of flow of the secretion play major roles in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 7 publications
1
36
0
Order By: Relevance
“…The concentrations of chemical contaminants in saliva have been shown to reflect their concentrations in plasma (4 ). Saliva sampling is noninvasive and has advantages over urine collection, particularly from young children still in diapers (7,9).…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of chemical contaminants in saliva have been shown to reflect their concentrations in plasma (4 ). Saliva sampling is noninvasive and has advantages over urine collection, particularly from young children still in diapers (7,9).…”
Section: Resultsmentioning
confidence: 99%
“…OF is a complex biological matrix consisting not only of the products generated by the secretary glands (parotid, submandibular and sublingual) that form saliva, but also Article published by EDP Sciences from secretions produced by minor glands (labial, buccal and palatal) as well as other substances such as bacteria, food debris, epithelial cells and gingival fluid [9][10][11]. The concentration of drugs in OF depends on the relative contribution of each gland since the transportation of drugs from plasma to saliva involves passive diffusion across lipid membranes, and different factors related to the chemical structure and nature of drugs play important roles in this mechanism [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of drugs in OF depends on the relative contribution of each gland since the transportation of drugs from plasma to saliva involves passive diffusion across lipid membranes, and different factors related to the chemical structure and nature of drugs play important roles in this mechanism [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…2 The use of saliva instead of blood has been proposed for therapeutic monitoring of theophylline, phenytoin, and other drugs. [3][4][5][6] Sampling saliva instead of blood is particularly valuable in infants and children because it is a painless, noninvasive procedure that averts blood volume loss. 6 A strong, significant linear correlation between saliva and serum concentrations of digoxin has been demonstrated in adults, [7][8][9] and in 1 study in infants.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Sampling saliva instead of blood is particularly valuable in infants and children because it is a painless, noninvasive procedure that averts blood volume loss. 6 A strong, significant linear correlation between saliva and serum concentrations of digoxin has been demonstrated in adults, [7][8][9] and in 1 study in infants. 10 However, another pediatric study 11 indicated that saliva digoxin concentration does not satisfactorily reflect plasma concentration.…”
Section: Introductionmentioning
confidence: 99%